Correlation of sense of coherence with oral health behaviors, socioeconomic status, and periodontal status - Kommuri Sahithi Reddy; Dolar Doshi; Suhas Kulkarni; Bandari Srikanth Reddy; Madupu Padma Reddy (Wolters Kluwer Medknow Publications, 2016)
Introduction: The sense of coherence (SOC) has been suggested to be highly applicable concept in the public health area because a strong SOC is stated to decrease the likelihood of perceiving the social environment as stressful. This reduces the susceptibility to the health-damaging effect of chronic stress by lowering the likelihood of repeated negative emotions to stress perception. Materials and Methods: The demographic data and general information of subjects' oral health behaviors such as frequency of cleaning teeth, aids used to clean teeth, and dental attendance were recorded in the self-administered questionnaire. The SOC-related data were obtained using the short version of Antonovsky's SOC scale. The periodontal status was recorded based on the modified World Health Organization 1997 pro forma. Results: The total of 780 respondents comprising 269 (34.5%) males and 511 (65.5%) females participated in the study. A significant difference was noted among the subjects for socioeconomic status based on gender (P = 0.000). The healthy periodontal status (community periodontal index [CPI] code 0) was observed for 67 (24.9%) males and 118 (23.1%) females. The overall SOC showed statistically negative correlation with socioeconomic status scale (r = −0.287). The CPI and loss of attachment (periodontal status) were significantly and negatively correlated with SOC. Conclusion: The present study concluded that a high level of SOC was associated with good oral health behaviors, periodontal status, and socioeconomic status.